Achieving Ultra-Wideband and Elevated Temperature Electromagnetic Wave Absorption via Constructing Lightweight Porous Rigid Structure - Jiao, Zibao; Huyan, Wenjun; Yang, Feng; Yao, Junru; Tan, Ruiyang; Chen, Ping; Tao, Xuewei; Yao, Zhengjun; Zhou, Jintang; Liu, Peijiang (Nano-Micro Letters, 2022)
Realizing ultra-wideband absorption, desirable attenuation capability at high temperature and mechanical requirements for real-life applications remains a great challenge for microwave absorbing materials. Herein, we have constructed a porous carbon fiber/polymethacrylimide (CP) structure for acquiring promising microwave absorption performance and withstanding both elevated temperature and high strength in a low density. Given the ability of porous structure to induce desirable impedance matching and multiple reflection, the absorption bandwidth of CP composite can reach ultra-wideband absorption of 14 GHz at room temperature and even cover the whole X-band at 473 K. Additionally, the presence of imide ring group in polymethacrylimide and hard bubble wall endows the composite with excellent heat and compressive behaviors. Besides, the lightweight of the CP composite with a density of only 110 mg cm−3 coupled with high compressive strength of 1.05 MPa even at 453 K also satisfies the requirements in engineering applications. Compared with soft and compressible aerogel materials, we envision that the rigid porous foam absorbing material is particularly suitable for environmental extremes. Highlights: 1 Constructing a porous carbon fiber/polymethacrylimide (CP) structure for acquiring promising electromagnetic absorption performance and withstanding both elevated temperature and high strength in a low density. 2 The absorption bandwidth of CP composite can reach ultra-wideband absorption of 14 GHz at room temperature and even cover the whole X-band at 473 K. 3 The lightweight of the CP composite with a density of only 110 mg cm−3 coupled with high compressive strength of 1.05 MPa even at 453 K.